2019
DOI: 10.1088/1748-0221/14/09/p09023
|View full text |Cite
|
Sign up to set email alerts
|

Design & analysis of a dual-band MIMO antenna to reduce the mutual coupling

Abstract: A compact dual wide-band multiple-input-multiple-output (MIMO) radiator is presented in this article. The MIMO radiator is developed on a 1.5 mm thick FR-4 substrate. The proposed structure is composed of U-shaped patches which are connected with small rectangular slit loaded circular rings and partial ground plane with chamfer edges. This arrangement is placed symmetrically at a far distance of 2.5 mm to achieve dual-operating bands with a high amount of isolation, radiation efficiencies and group delay betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Secondly, for a system with highly efficient antennas (>90%), the ECC can be calculated in terms of S-parameters, as expressed in equation (2). The S-parameters technique, shown in equation (2) [37], demonstrates a different technique for calculating ECC.…”
Section: Mimo Antenna Parametersmentioning
confidence: 99%
“…Secondly, for a system with highly efficient antennas (>90%), the ECC can be calculated in terms of S-parameters, as expressed in equation (2). The S-parameters technique, shown in equation (2) [37], demonstrates a different technique for calculating ECC.…”
Section: Mimo Antenna Parametersmentioning
confidence: 99%
“…Evaluating ECC using far-field radiation parameters takes a long time and much effort. Another method described in [ 29 ] for finding ECC using the S-parameters approach is shown in Equation (2). …”
Section: Mimo Antenna Parametersmentioning
confidence: 99%
“…A comparison between the introduced MIMO antenna characteristics and the references (Rezvani and Zehforoosh, 2018; Babu et al, 2019) is listed in Figure 14. It is observed that the proposed antenna has the highest frequency band coverage compared to other designs despite the low complexity of the structure.…”
Section: Design Of Multi-input Multi-output Antennamentioning
confidence: 99%
“…Multi-input multi-output (MIMO) antennas are a good solution for the mentioned issues. Also, there are lots of designs introduced in the recent years, such as Rezvani and Zehforoosh (2018), Aw et al (2019), Babu et al (2019). MIMO antennas were designed for the most of the wireless technology systems including Bluetooth and WLAN.…”
Section: Introductionmentioning
confidence: 99%